Clinical and epidemiological characteristics of scarlat fever in children - T. M. Chernova; D. O. Ivanov; T. V. Kosenkova; V. N. Timchenko; V. F. Sukhovetskaya; O. V. Bulina; I. Yu. Bazunova; A. A. Zherebtsova (Журнал инфектологии, 2025)
In recent years, there has been an increase in the incidence of scarlet fever in the world, especially in urban areas with higher population density and more developed transport infrastructure.Objective: to study the clinical and epidemiological features of modern scarlet fever in children in St. Petersburg to assess the development trends of the epidemic process and the effectiveness of anti-epidemic measures.Materials and methods: a retrospective analysis of the medical records of a children’s clinic for 2015-2023 was carried out. The diagnosis was established on the basis of clinical data and laboratory examination results: sowing of discharge from the pharynx for group A streptococcus (GAS), determination of group-specific antigens of GAS in discharge from the pharynx using a commercial test system.Results: until 2018, the situation with the incidence of scarlet fever in the observed children remained stable with a downward trend. In 2019, another increase in the incidence began. The COVID-19 pandemic interrupted the negative trend, but after the lifting of restrictive measures in 2023, the incidence rate continued to increase. Over the entire multiyear period, the number of cases in foci was limited to 1-3 cases, and the duration of outbreaks did not exceed 1-2 months. Even during the lockdown, the characteristic winter-spring seasonality of scarlet fever remained. However, in 2023, an off-season peak in incidence was noted (March-May) with the formation of 23 foci in the service area of the children’s clinic, 18 of which were observed in preschool organizations. 91.2% of outpatient children suffered from mild scarlet fever, 8.8% – in a moderate form.Conclusion: the epidemiology of scarlet fever has not changed significantly in the last decade. However, as the experience of the COVID-19 pandemic has shown, strict restrictive measures can significantly affect the incidence rate.